2016
DOI: 10.3389/fpsyg.2016.01334
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Influences on Moral Judgments: East–West, Male–Female, and Young–Old

Abstract: Gender, age, and culturally specific beliefs are often considered relevant to observed variation in social interactions. At present, however, the scientific literature is mixed with respect to the significance of these factors in guiding moral judgments. In this study, we explore the role of each of these factors in moral judgment by presenting the results of a web-based study of Eastern (i.e., Russia) and Western (i.e., USA, UK, Canada) subjects, male and female, and young and old. Participants (n = 659) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 104 publications
5
42
0
1
Order By: Relevance
“…Perhaps older adults belong to a more consequentialist, outcome-focused, generation than younger adults. However, this possibility is inconsistent with the results reported by Arutyunova, Alexandrov, and Hauser (2016) who found that, when evaluating trolley dilemmas, older adults turned out to be more deontological and less consequentialist than younger adults (see also Hannikainen, Machery, & Cushman, 2018, who argue that younger cohorts are becoming more utilitarian). Future studies could investigate whether these effects generalize to the evaluation of other moral cases, in particular ones likely to be encountered in everyday situations.…”
Section: Limitationsmentioning
confidence: 57%
“…Perhaps older adults belong to a more consequentialist, outcome-focused, generation than younger adults. However, this possibility is inconsistent with the results reported by Arutyunova, Alexandrov, and Hauser (2016) who found that, when evaluating trolley dilemmas, older adults turned out to be more deontological and less consequentialist than younger adults (see also Hannikainen, Machery, & Cushman, 2018, who argue that younger cohorts are becoming more utilitarian). Future studies could investigate whether these effects generalize to the evaluation of other moral cases, in particular ones likely to be encountered in everyday situations.…”
Section: Limitationsmentioning
confidence: 57%
“…The preference for Switch over Footbridge is already well documented. Because this preference is large, it is easy to detect even with small samples, and it was, indeed, detected in at least 30 countries (21)(22)(23)(24)(25). The difference between Switch and Loop is smaller and requires larger sample sizes.…”
Section: C B Amentioning
confidence: 99%
“…Previous studies have indicated age and gender differences in moral judgment. Females express less preference for utilitarian options than males, while the older made less utilitarian judgments than the younger (e.g., Arutyunova et al, 2016 ). Friesdorf et al (2015) found that females had higher deontological inclinations than males.…”
Section: Resultsmentioning
confidence: 99%